The Interplay between Defensins and Microbiota in Crohn’s Disease - Lorena Coretti; Alessandro Natale; Mariella Cuomo; Ermanno Florio; Simona Keller; Francesca Lembo; Lorenzo Chiariotti; Raffaela Pero (Mediators of Inflammation)
Crohn’s disease (CD) is a chronic inflammation of the intestinal mucosa, characterized by periods of acute recurrence and remission. Depending on the specific region affected, CD is classified as ileal CD or colonic CD. It is largely accepted that the intestinal microbiota is involved in the onset of the pathology. Indeed, a reduced immune tolerance to components of the intestinal commensal microbiota and inflammation of the intestinal barrier typifies patients with CD. Several studies have shown defective expression of intestinal antimicrobial peptides (AMPs) in patients with CD compared to controls, particularly defensins. A reduction in α-defensins is observed in ileal CD, while β-defensins are increased in colonic CD. In addition to an immunological basis, the disease is frequently associated with genetic alterations including mutations of NOD2 gene. Several therapeutic strategies to circumvent the dysfunction observed in CD are currently under investigation. These include the use of delivery systems to administer endogenous AMPs and the engineering of peptidomimetics that could ameliorate the severity of CD. In this review, the role defensins play in CD and the strategies aimed at overcoming bacterial resistance will be discussed.